Tumor treating fields combined with a poly (adenosine diphosphate-ribose) polymerase inhibitor during radiotherapy for rapidly progressing IDH-wildtype diffuse astrocytoma: a case report - Zheng Wang; Yi Ren; Fangfang Du; Yafang Sun; Wei Jiang (Journal of International Medical Research, 2021)
A 57-year-old woman was diagnosed with IDH-wildtype (IDHwt) astrocytoma (World Health Organization grade II) with the molecular characteristics of glioblastoma. She underwent concurrent radiotherapy and chemotherapy according to the Stupp protocol in combination with a multi-target antiangiogenic drug and additional intrathecal chemotherapy using methotrexate. During treatment, the patient’s tumor showed rapid progression. The chemotherapy with temozolomide was stopped and replaced with radiotherapy combined with tumor treating fields (TTF), the poly (adenosine diphosphate-ribose) polymerase (PARP) inhibitor niraparib, and anlotinib. After the radiotherapy was completed, the symptoms of increased intracranial pressure and epilepsy were well controlled. Considering the patient’s tolerance to the treatment, the combined therapy of TTF and anlotinib was continued, and osimertinib, a third-generation epidermal growth factor receptor–tyrosine kinase inhibitor with good permeability of the blood–brain barrier, was added. The patient was regularly followed up and had no obvious adverse drug reactions. Head magnetic resonance imaging (plain scan + enhanced scan) suggested that the lesions were stable. For rapidly progressing glioblastomas or histological grade II/III IDHwt astrocytomas, the combination of TTF and a PARP inhibitor during radiotherapy may have a synergistic effect on tumor control and is well tolerated by patients.